Antioxidant activity of proteins extracted from red alga dulse harvested in Japan. Issue 2 (29th October 2018) - Sato, Naoto; Furuta, Tomoe; Takeda, Tomoyuki; Miyabe, Yoshikatsu; Ura, Kazuhiro; Takagi, Yasuaki; Yasui, Hajime; Kumagai, Yuya; Kishimura, Hideki
Abstract: In this study, we investigated antioxidant activity of proteins from the red alga dulse ( Palmaria sp.) harvested in Hokkaido, Japan. The dulse proteins that contain phycoerythrin (PE) as the main component showed a high radical scavenging activity. To clarify the key constituent of antioxidant activity in dulse proteins, we prepared recombinant dulse PE β‐subunit (rPEβ) (apoprotein) and chromophores from the dulse proteins. As a result, the rPEβ showed lower radical scavenging activity than that of dulse proteins. On the other hand, the dulse chromophores composed mainly of phycoerythrobilin (PEB) indicated extremely higher radical scavenging activity (90.4% ± 0.1%) than that of dulse proteins (17.9% ± 0.1%) on ABTS assay. In addition, on cell viability assay using human neuroblastoma SH‐SY5Y cells, the dulse chromophores showed extracellular and intracellular cytoprotective effects against H2 O2 ‐induced cell damage. From these data, we concluded that the dulse proteins have antioxidant ability and the activity principally derives from the chromophores. Practical application: Dulse is an abundant and underused resource, which contains a lot of proteins, especially phycoerythrin. We here demonstrated that the practically prepared dulse proteins possessed antioxidant activity and clarified that chromophores from the dulse proteins were the key components. Therefore, the dulse proteins have a potential for functional material.